Financial Independence and Investment Behaviour of University Students: A Qualitative Evidence - Pranoto Effendi; Muhammad Isman Almaududi (Lembaga Pengembangan Kinerja Dosen, 2024)
University students have a strategic role to play in economic sphere. They are part of generation Z that will make up a lot of proportion of population in the near future. Encouraging them early into labour market and investment activities will benefit both of them and the economy where they live. This article aims to understand the financial independence of university students and their investment behaviour during their study. With 76 university students as respondents, a qualitative method is utilised to examine the part time job they seek and the investment endeavour they commit to. The chi-square test is applied and the findings reveal that there is no gender association with part time job, but on the contrary, there is with investment activity. Male students are found to be more active in investment than female counterparts. There is also no association between part time job and investment activity for both male and female students. The male students tend to go for higher risk type and more variety of investment than those of female students. The findings have implication and future research for entrepreneurial education and promotion of student career and investment program.